(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
Starting from the analysis of the decision of the Italian Constitutional Court on the “Cappato case”, the essay is the occasion for a joint reflection between Italian constitutional law and comparative law on the subject of assisted suicide and euthanasia, which seems to determine the inertia of the legislators in the face of activism of the Courts, perpetually seeking a dialogue with the first. To suffer the most serious damage of these attitudes are the sick, who in this matter more than ever need certainty to the law.